THE PREDICTIVE EFFECT OF PSYCHOLOGICAL RESILIENCE ON THE LEVELS OF PSYCHOLOGICAL INFLEXIBILITY OF ADOLESCENTS - VANGÖLÜ, Mehmet Sıddık; TANHAN, Fuat (SSD Journal, 2022)
The aim of this study is to examine the predictive effect of psychological resilience on adolescents' levels of psychological inflexibility. The study group of the research consists of adolescents aged between 15 and 17 who attend the 10th and 11th grades in the 2021-2022 academic year. A total of 304 adolescents, 146 women, and 158 men participated in the study. Avoidance and Fusion Questionnaire –Youth 8 (AFQ-Y8), and Resiliency Attitude and Skills Profile (RASP), were used for data collection. Pearson correlation analysis was used to reveal whether there was a relationship between the variables of the study, and multiple linear regression analysis was used to examine the predictive relationship between the variables. According to the findings of the study, there was a negative and significant relationship between psychological inflexibility and humor, independence, and values, while the relationship between insight and psychological inflexibility was not statistically significant and it was determined that resilience predicted psychological inflexibility by 14%. In other words, it can be said that humor, independence, and insight, which are the subdimensions of psychological resilience, respectively, are significant predictors of psychological inflexibility.